Une architecture contemporaine remarquable au sein d’un parc historique - Sylvie Denante (In Situ)
In October 2019, the École supérieure d’art d’Aix-en-Provence Félix-Ciccolini (ESAAIX) was awarded the label “Architecture contemporaine remarquable” (“Remarkable Contemporary Architecture”) by the French Ministry of Culture. The building, designed by the architect Claude Pradel-Lebar and delivered in 1977, implemented the recommendations issued a few years earlier for the construction of higher education institutions after 1968. From now on, their architecture will express a desire for modernity, fluidity and transparency.But ESAAIX is also faced with other, strictly local issues: a historical, landscaped, urban and above all monumental environment: the new school is in fact adjacent to one of Aix’s most highly reputed historical monument: the Pavillon Vendôme. It was the adaptation of a thought to a specific context that guided Claude Pradel-Lebar’s creative approach and gave the Aix School of Art its specificity.